A method to produce hydrazide - Wan Yunus, Wan Md. Zin; Tuan Ismail, Tuan Noor Maznee; Abu Hassan, Hazimah (2011)
A method to produce hydrazide from triacylglycerol, the method includes steps of mixing vegetable oil with an organic solvent in a reactor forming a mixture, adding hydrazine monohydrate into the mixture, stirring the mixture, adding catalyst, stirring the mixture to form hydrazide and separating the hydrazide from the mixture.